Tissue-Specific Regulation of Gma-miR396 Family on Coordinating Development and Low Water Availability Responses - Liu, Weican; Zhou, Yonggang; Li, Xiaowei; Wang, Xingchao; Dong, Yuanyuan; Wang, Nan; Liu, Xiuming; Chen, Huan; Yao, Na; Cui, Xiyan; Jameel, Aysha; Wang, Fawei; et al. (Frontiers in Plant Science, 2017)
Previously, it was reported that miR396s interact with growth-regulating factors (GRFs) to modulate plant growth, development, and stress resistance. In soybean, 11 gma-miR396 precursors (Pre-miR396a–k) were found, and 24 GmGRFs were predicted as targets of seven mature gma-miR396s (gma-miR396a/b/c/e/h/i/k). To explore the roles of the miR396–GRF module in low water availability response of soybean, we analyzed the expression of Pre-miR396a–k, and found that Pre-miR396a/i/bdgk/e/h were up-regulated in leaves and down-regulated in roots; on the contrary, GmGRF5/6/7/8/15/17/21 were down-regulated in leaves and GmGRF1/2/17/18/19/20/21/22/23/24 were up-regulated in roots of low water potential stressed soybean. Any one of gma-miR396a/b/c/e/h/i/k was able to interact with 20 GmGRFs (GmGRF1/2/6–11/13–24), confirming that this module represents a multi-to-multi network interaction. We generated Arabidopsis plants over-expressing each of the 11 gma-miR396 precursors (Pre-miR396a–k), and seven of them (miR396a/b/c/e/h/i/k-OE transgenic Arabidopsis) showed altered development. The low water availability of miR396a/b/c/e/h/i/k-OE was enhanced in leaves but reduced in seeds and roots. Contrary to previous reports, miR396a/b/c/i-OE seedlings showed lower survival rate than WT when recovering after rewatering under soil drying. In general, we believe our findings are valuable to understand the role of gma-miR396 family in coordinating development and low water availability responses, and can provide potential strategies and directions for soybean breeding programs to improve seed yield and plant drought tolerance.